2020
DOI: 10.3389/fneur.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of the “Weekend Effect” in the Northern New South Wales Telestroke Network

Abstract: Background: Admission outside normal business hours has been associated with prolonged door-to-treatment times and poorer patient outcomes, the so called "weekend effect. " This is the first examination of the weekend effect in a telestroke service that uses multi-modal computed tomography. Aims: To examine differences in workflow and triage between in-hours and out-of-hours calls to a telestroke service. Methods: All patients assessed using the Northern New South Wales (N-NSW) telestroke service from April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Only 1 study reported on interactions between health care providers, which was asynchronous [ 74 ]. Seven videoconference initiatives required patients to attend a local health care facility to use videoconference equipment [ 18 , 19 , 21 - 27 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 study reported on interactions between health care providers, which was asynchronous [ 74 ]. Seven videoconference initiatives required patients to attend a local health care facility to use videoconference equipment [ 18 , 19 , 21 - 27 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In that trial, all patients were clinically assessed by a neurologist using NIHSS. Comparing different telestroke protocols from Europe ( 18 ), Australia ( 19 ), and the US ( 20 ), we learned that the local conditions define certain characteristics. While older publications consider any telemedical approach to stroke medicine, newer publications, such as the ESO 2019 guidelines, refer to any real-time video–audio connection as telestroke.…”
Section: Discussionmentioning
confidence: 99%
“…Time metrics were also assessed using a regression model. To examine the effect of telestroke experience, we set treatment timings as a dependent variable and set the time elapsed since January 2017, NIHSS, ED arrival within 4.5 h from the onset, and reperfusion therapy as independent variables, since our previous research showed symptom severity, fast ED arrival and reperfusion therapy related to faster treatment timings (15). Partial missing data from the database are random and the proportion of cases missing data was relatively small, thus we used the case deletion method.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 109 patients who received reperfusion therapy, the median age was 73 [64-80] years and 66 were male (60.6%), and most of them (98.2%) were independent at baseline. The baseline NIHSS was 9 [6][7][8][9][10][11][12][13][14][15], and 84 (77.1%) had a large vessel occlusion. The baseline characteristics between phase 1 and 2 for these patients were similar, but there was a higher proportion of male sex in phase 1 (69.1% in phase 1 vs. 46.3% in phase 2, p = 0.02) and a higher proportion of large vessel occlusion strokes in phase 2 (70.6 vs. 87.8%, p = 0.04).…”
Section: Reperfusion Therapy Subgroupmentioning
confidence: 99%